2009
DOI: 10.1111/j.1471-4159.2008.05866.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Alzheimer’s amyloid toxicity with a tricyclic pyrone molecule in vitro and in vivo

Abstract: Small β‐amyloid (Aβ) 1–42 aggregates are toxic to neurons and may be the primary toxic species in Alzheimer’s disease (AD). Methods to reduce the level of Aβ, prevent Aβ aggregation, and eliminate existing Aβ aggregates have been proposed for treatment of AD. A tricyclic pyrone named CP2 is found to prevent cell death associated with Aβ oligomers. We studied the possible mechanisms of neuroprotection by CP2. Surface plasmon resonance spectroscopy shows a direct binding of CP2 with Aβ42 oligomer. Circular dichr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 58 publications
5
59
0
Order By: Relevance
“…Epidemiological studies have suggested that curcumin contributes to the reported 4.4-fold reduced (age-adjusted) prevalence of AD in India compared with the United States (16). Both in vitro and in vivo studies have shown that curcumin can bind to amyloid and inhibit A␤ aggregation (14,17), as well as fibril and oligomer formation (14). In vivo studies have shown that dietary curcumin can cross the blood-brain barrier and significantly decrease A␤ deposition and plaque burden in AD transgenic mice (14,15,18,19), markedly inhibit Tau phosphorylation (20), and attenuate inflammation and reduce oxidative damage (14,18), and reduce genomic instability events (21).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…Epidemiological studies have suggested that curcumin contributes to the reported 4.4-fold reduced (age-adjusted) prevalence of AD in India compared with the United States (16). Both in vitro and in vivo studies have shown that curcumin can bind to amyloid and inhibit A␤ aggregation (14,17), as well as fibril and oligomer formation (14). In vivo studies have shown that dietary curcumin can cross the blood-brain barrier and significantly decrease A␤ deposition and plaque burden in AD transgenic mice (14,15,18,19), markedly inhibit Tau phosphorylation (20), and attenuate inflammation and reduce oxidative damage (14,18), and reduce genomic instability events (21).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…Solutions of oligomeric Ab 1-42 were prepared as described previously. 49 To prepare the oligomer solution, monomeric Ab 1-42 peptides were incubated with PBS at 4 1C for 24 h and immediately stored in aliquots at À 80 1C. To examine the effect of DBP on oligomeric Ab 1-42 formation, peptide solutions containing Ab 1-42 monomers (10 mM) with and without DBP (100 mg/ml) were incubated at 4 1C for 24 h. DBPfree samples were treated with the same volume of distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Curcumin is an active principle of the perennial herb Curcuma longa (commonly known as turmeric) which is used in the Indian traditional diet and as herbal medicine [13]. Recent studies indicate a role for curcumin as a potential anti-amyloid agent in vitro [14][15][16] and in vivo [17,18]. However, curcumin is unstable in aqueous media [19] and presents low bioavailability following delivery through oral or parenteral route [20].…”
Section: Introductionmentioning
confidence: 99%